Mechanism For Checking BKK and Survey Fee Transaction Notes At KJPP SISCO - Aurelia Selvira Oliviani; Sri Trisnaningsih (International Journal Business, Management and Innovation Review, 2025)
Checking cash receipts provides important benefits for companies, such as ensuring expenditures comply with policy, increasing financial transparency, ensuring compliance with accounting standards, optimizing cost control, and preparing for external audits. Without these checks, the risk of fraud, misappropriation of funds, and non-compliance with regulations increases, and financial transparency decreases. At KJPP SISCO, checking Cash Out Proofs, Daily Cash Reports and transaction records prevents fraud and maintains the integrity of financial data. This process includes document verification, report matching, and transaction compliance evaluation. These regular checks ensure that all expenses are recorded correctly and transparently, and prepare the company well for external audits.